Digitalisasi Wisata di Desa Wisata - Ais Tsurayya Mumtaz; Mila Karmilah (Jurnal Kajian Ruang, 2022)
ABSTRACTThe digitization of tourism is one of the important strategies in addressing a digital-oriented civilization in meeting their needs for travel. The digitization of tourism is considered as the right step in promoting tourism through a digital approach that has an impact on the development of tourism potential in a tourist village. The analytical method used in this research is a qualitative analysis method by analyzing the content and / or analysis of the literature review. Strategies that can be carried out in digitizing tourism in tourist villages are to improve the management of tourist villages, tourism village infrastructure, digitalization forms of wsata villages, and management of tourism digitization. The results of the study findings in several case studies are that by developing tourist villages and digitizing tourism, it has been proven that many benefits are obtained, such as the ease in providing tourism services to tourists including access in the context of carrying out marketing, making it easier for tourists to access information about a tourism destination and minimizing costs both for organizers and / managers, as well as for tourists. With digitalization in tourist villages, it can indirectly increase people's income and lead to an increase in the regional economy.Keywords: Tourist village, Tourism digitization. ABSTRAKDigitalisasi wisata merupakan salah satu strategi penting dalam menyikapi peradaban masyarakat yang berorientasi digital dalam memenuhi kebutuhan mereka untuk berwisata. Digitalisasi wisata dianggap sebagai langkah tepat dalam mempromosikan wisata melalui pendekatan digital yang berdampak pada pengembangan potensi wisata di suatu desa wisata. Metode analisis yang digunakan dalam penelitian ini adalah metode analisis kualitatif dengan menganalisis isi dan/atau analisis literatur review. Strategi yang dapat dilakukan dalam digitalisasi wisata pada desa wisata adalah dengan meningkatkan pengelolaan desa wisata, infrastruktur desa wisata, bentuk digitalisasi desa wsata, dan pengelolaan digitalisasi wisata. Hasil temuan studi pada beberapa studi kasus adalah dengan pengembangan desa wisata dan digitalisasi wisata terbukti diperoleh banyak manfaat, seperti kemudahan dalam memberikan jasa layanan pariwisata kepada wisatawan termasuk akses dalam rangka penyelenggaraan pemasarannya, mempermudah wisatawan dalam mengakses informasi tentang suatu destinasi pariwisata serta meminimalisir biaya baik bagi pihak penyelenggara dan/pengelola, maupun bagi wisatawan. Dengan adanya digitalisasi di desa wisata secara tidak langsung dapat meningkatkan pendapatan masyarakat dan berujung pada peningkatan perkonomian daerah.Kata Kunci: Digitalisasi wisata, Desa wisata.